KAJIAN AKSES MASYARAKAT DALAM PENGELOLAAN GALIAN PASIR DI SUB DAERAH ALIRAN SUNGAI CIATEN, CISADANE HULU - Messalina Lovenia Salampessy; Indra Gumay Ferbyano; Andi Chairil Ichsan; Ina Lindiawati (Forestry Study Program University Of Mataram, 2020)
Community access to obtain, control and regulate the use of natural resources around watersheds (DAS) will have an influence on the sustainability of the functions and roles of the watershed. This study aims to describe and explain the access of the community in the utilization of excavated C resources around the watershed. This research was conducted in May-October 2017 in the village of Cemplang, Cibungbulang, Bogor, especially in the Ciaten Cisadane Hulu sub-watershed. Data obtained through in-depth interviews and focus group discussions (FGD) were then analyzed qualitatively using the theory of access from Ribot and Peluso. The results show that various stakeholders / actors were directly involved in natural resource utilization activities in excavation C, especially in sand mining activities in Cemplang village, among others: Village government, mining landowners / entrepreneurs and communities around the sand mining land. Each actor has different interests in the existence of a watershed both socially, economically and ecologically; as well as the power they have. Therefore, the management of the natural resources of the watershed must be carried out in a participatory and adaptive manner so that the sustainability of the watershed functions remains sustainable.access, actors, upstream Cisadane watershed, excavation C.